Proteinuria in Adults with Severe Dengue Fever - Awais, Muhammad; Khan, Inam Ullah; Khan, Hanif Ullah; Khan, Zakir; Waheed Ullah; Khan, Almas (Indus Journal of Bioscience Research, 2025)
Background: The mosquito-borne viral illness known as Dengue fever now threatens public health in Pakistan and other tropical nations. Profound cases of dengue frequently generate medical difficulties which transcend the bloodstream although renal damage is one of the main extra-hematological consequences. Renal injuries manifest first through proteinuria which experts now recognize as a warning sign of dengue disease among patients with severe manifestations. Objective: This research investigated how often proteinuria occurred among adult hospital patients who suffered severe dengue infection and examined the relationship between this condition and patient characteristics. Methods: Researchers from KTH Peshawar performed their study via a cross-sectional approach throughout six months. A research study included 100 patients within the age range of 18 to 60 years who experienced severe dengue without pre-existing renal, hepatic or cardiovascular medical conditions. The evaluation of proteinuria employed urine dipstick testing as the diagnostic method. The study analysis utilized SPSS v26 to process both clinical and demographic information. Results: In 56% of the patients, proteinuria was detected. The prevalence was the same across genders and age groups, without any significant differences. Nevertheless, proteinuria was significantly associated (p = 0.02) with a higher BMI (≥25). Proteinuria was also significantly related to elevated serum creatinine (p < 0.01) and suggests early renal involvement. Conclusion: Proteinuria is a common finding in adults with severe dengue fever, and could be a useful marker of renal impairment. Early detection of renal complications is facilitated by routine screening using dipstick analysis, especially in settings with high burden, which should ultimately lead to better patient outcome. Its prognostic implications need to be further explored through further longitudinal studies.